Pola Komunikasi Pengurus Masjid Dalam Memakmurkan Masjid Jami Al-Awwabin Surabaya - Budiono, Bagas Setyawan; Murtadlo , Athok (LPPM Stikosa-AWS, 2024)
The management of Jami' Al-Awwabin Mosque Surabaya is a community religious organization formed to prosper the mosque and make the mosque the center of Muslim activities both religious and social society. The purpose of this study is to determine the Communication Pattern of Mosque Management in Prospering Jami'Al-Awwabin Mosque Surabaya. This research uses a descriptive qualitative approach method. Researchers obtain data by conducting interviews, observations, and documentation. The resource persons in this study were the Management of Jami' Al-Awwabin Mosque starting from the chairman, vice chairman, secretary, religious section and assembly, and active worshippers. Based on the results of field research that the management of Jami' Al-Awwabin Mosque did. Based on the results of field research that the management of the Jami' Al-Awwabin Mosque conveys information with a wheel communication pattern making the chairman of the mosque management an information center between the management and worshippers who occupy a central position. Meanwhile, between members with a circular communication pattern, the information process rolls from the chairman to the vice chairman and then to the secretary who forwards to other sections until there is reciprocity to the chairman. The pattern of interpersonal communication also occurs when the head of the mosque management approaches the congregation including greeting each other and shaking hands, the approach to members is also carried out chatting casually if they find difficulties in carrying out their duties. Factors supporting the communication pattern of Jami'Al-Awwabin Mosque are the community environment, activities, and facilities provided within the mosque. While the inhibiting factor is the time of mosque administrators who are busy with their work as a social community.